Changes in expression of GFAP in ganglion of Procambarus virginalis under conditions of temperature stress - O. M. Marenkov; O. S. Nesterenko; I. I. Borovyk; Y. P. Kovalchuk; V. O. Kurchenko; I. V. Holub (Regulatory Mechanisms in Biosystems, 2025)
The issue of neurophysiological reactivity of invertebrates, especially invasive species, in response to environmental stress factors, in particular temperature changes, still remains poorly studied. Due to the genetic homogeneity of the offspring, the ma r bled crayfish Procambarus virginalis (Lyko, 2017) (Decapoda, Cambaridae) is unique for studying these issues – a parthenog e netic invasive species that demonstrates high adaptability to various environmental conditions. This work presents studies on changes in GFAP expression in the nervous system of P . virginalis under the influence of extremely low water temperatures for this species (+9 °C) and elevated temperatures (+23 and +26 °C) in order to assess the glial response to stress. The supraphary n geal ganglion was isolated, cytoskeletal protein extraction was performed, and GFAP immunoblotting using polyclonal antib o dies was performed. Quantitative assessment of GFAP expression was performed by densitometry. No statistically significant changes in the protein content in the cytoskeletal fraction of the nervous tissue of crayfish were detected. In the control group, weak expression of GFAP was detected, the highest level of expression was observed in group 2 – cold stress, in which a large number of shortened GFAP polypeptides (~ 35 kDa) was also detected. In the control, the intensity of the 49 kDa band was 0.12 ± 0.05 a.u. The largest increase in GFAP content compared to the control was detected in group 2 under cold stress – 0.38 ± 0.07 a.u. Temperature stress induces glial cell activation in P. virginalis , similar to reactive gliosis in vertebrates. GFAP expression and its proteolytic changes can be used as early indicators of neurostress in invertebrates. These results emphasize the feasibility of using GFAP as a biomarker for assessing neurotoxic effects of the environment in crustaceans. Monitoring GFAP levels in ma r bled crayfish is promising for assessing the impact of environmental factors on their adaptive capabilities.